Pendapat Warga Gunung Anyar Jaya I Tentang Pentingnya Kegiatan Kerja Bakti Di Era Globalisasi - Natasya Christie Susilo; Elena Margareta Pitono (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Community work activities still exist in Indonesia, especially in Gunung Anyar Jaya I, and have important benefits. Through this activity, the community can clean up the environment, repair damaged roads, and rebuild public facilities that have been damaged such as places of worship, bridges, and schools. In addition to its benefits in infrastructure development, community work activities can also increase a sense of unity and togetherness among the community, creating a harmonious and peaceful environment. Therefore, it is important to maintain Indonesian cultural traditions and values by carrying out community work activities. Despite its benefits, community work activities are often neglected in the current era of globalization. However, in the context of Gunung Anyar Jaya I, this activity must be carried out to improve infrastructure and the surrounding environment, as well as increase a sense of unity and togetherness among the community. Community work activities can be an opportunity to foster a sense of mutual help and support among the community. With more people participating in this activity, it will be easier to clean up the environment and repair damaged public facilities.Â